2019
DOI: 10.21203/rs.2.15433/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards an understanding of the burdens of medication management affecting older people: the MEMORABLE realist synthesis

Abstract: Background Increasing numbers of older people are living in the community with multiple diagnoses and medications. Managing multiple medications produces issues of unrivalled complexity for those involved. Despite a growing body of literature on the subject, gaps remain in understanding how, why and for whom complex medication management works, and therefore how best to improve practice and outcomes. MEMORABLE, MEdication Management in Older people: Realist Approaches Based on Literature and Evaluation, aimed … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 42 publications
1
8
1
Order By: Relevance
“…This study identified some similar barriers and facilitators to successful medicines management for PwD to those already identified in the literature, such as the importance of carers, having supportive and trusting relationships with healthcare professionals, carers' desire for further information about medicines, and use of cues and reminder strategies 15,16,18,20,21,41,48 . However, we also report some contrasting findings.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This study identified some similar barriers and facilitators to successful medicines management for PwD to those already identified in the literature, such as the importance of carers, having supportive and trusting relationships with healthcare professionals, carers' desire for further information about medicines, and use of cues and reminder strategies 15,16,18,20,21,41,48 . However, we also report some contrasting findings.…”
Section: Discussionsupporting
confidence: 77%
“…This is one of only two studies, to our knowledge, to use a theory‐based approach to explore experiences of community‐dwelling PwD and their carers about medicines management, and determine beliefs of PwD about medicines 41 . It extends a limited evidence base to provide valuable findings for future intervention development to improve medicines management for PwD.…”
Section: Discussionmentioning
confidence: 99%
“…The MEdication Management in Older people: Realist Approaches Based on Literature and Evaluation (MEMORABLE) study was funded by the National Institute for Health Research (NIHR), the research arm of the NHS 12,13 …”
Section: The Memorable Studymentioning
confidence: 99%
“…The MEdication Management in Older people: Realist Approaches Based on Literature and Evaluation (MEMORABLE) study was funded by the National Institute for Health Research (NIHR), the research arm of the NHS. 12,13 It used a novel and innovative research technique, called realism, to understand the challenges associated with medication management for older people living in the community, taking many different medications, and their family carers. From this, the framework for interventions to address some of the identified challenges was developed.…”
Section: The Memorable Studymentioning
confidence: 99%
“…In this regard, information campaigns have been devised on the role of patients in the safe use of medication, reinforcing its role as a final barrier to adverse events [21]. Research focuses on medication management to provide data on what interventions work and their key points [22].…”
Section: How It Has Been Handled Up To Nowmentioning
confidence: 99%